Reevaluating Approaches to Religious Moderation at the Grassroots Level: The Role of Muslim Youth in Advancing Interfaith Dialogue - Jati, Wasisto; Syamsurijal, Syamsurijal; Halimatusa'diah, Halimatusa'diah; Aji, Gutomo; Yilmaz, Ihsan (Al-Jami'ah Research Centre, 2024)
This paper examines the potential role of Muslim youth as alternative partners in fostering religious moderation at the grassroots level. It identifies two central issues in current religious moderation policies in Indonesia: (1) an overemphasis on programs aimed at security and deradicalization, which overshadow initiatives that encourage harmonious inter- and intra-religious relationships, and (2) a predominantly top-down approach that limits grassroots participation, particularly among young people. These challenges expose gaps in policy strategies and highlight unequal public engagement in religious moderation efforts led by the government. Addressing these concerns, the study proposes alternative policy strategies that actively involve Muslim youth, who bring their own understanding of religious moderation cultivated through participation in various Islamic organizations and youth forums. This study adopts a qualitative research methodology, incorporating data from in-depth interviews with students, academics, and activists; direct observations of interfaith dialogue groups and communities; and document analysis. Fieldwork was conducted in Semarang and Yogyakarta—cities renowned for their robust interfaith dialogue networks and advocacy in Indonesia. The paper ultimately argues that Muslim youth’s active involvement in interfaith dialogue is a viable strategy to expand engagement at the grassroots level, especially among marginalized communities or those disadvantaged by hierarchical religious moderation policies.[Tulisan ini mengkaji peran muda-mudi muslim sebagai mitra alternatif dalam implementasi moderasi beragama di tingkat akar rumput. Ada dua permasalahan yang perlu digarisbawahi terkait kebijakan moderasi beragama: 1) program yang berorientasi pada keamanan dan deradikalisasi lebih besar daripada upaya membangun keharmonisan hubungan antar/intra umat beragama dalam kebijakan moderasi beragama, 2) pendekatan top-down tidak mengakomodasi partisipasi dari bawah khususnya generasi muda. Kedua permasalahan ini menimbulkan kesenjangan antara strategi kebijakan dan respons masyarakat terhadap program moderasi beragama yang dilakukan pemerintah. Berangkat dari permasalahan tersebut, tulisan ini menawarkan alternatif strategi kebijakan yang melibatkan generasi muda, yang mempunyai definisi tersendiri mengenai moderasi beragama melalui keterlibatan mereka dalam beberapa organisasi Islam dan forum kepemudaan lainnya. Tulisan ini menggunakan metode penelitian kualitatif dengan data berupa hasil wawancara mendalam dengan mahasiswa, akademisi, dan aktivis; observasi langsung pada kelompok/komunitas dialog antaragama; dan analisis dokumen. Penelitian lapangan dilakukan di Semarang dan Yogyakarta, dua kota di Indonesia yang memiliki jaringan dan advokasi dialog antaragama yang baik. Penelitian ini menunjukkan bahwa keterlibatan generasi muda dalam dialog antaragama dapat menjadi strategi alternatif untuk menjangkau lebih banyak komunitas di tingkat akar rumput, terutama kelompok masyarakat yang menyandang status minoritas dan posisi yang tidak terfasilitasi akibat kebijakan moderasi beragama yang bersifat hierarkis.]